2022
DOI: 10.1371/journal.ppat.1011041
|View full text |Cite
|
Sign up to set email alerts
|

Nsp1 proteins of human coronaviruses HCoV-OC43 and SARS-CoV2 inhibit stress granule formation

Abstract: Stress granules (SGs) are cytoplasmic condensates that often form as part of the cellular antiviral response. Despite the growing interest in understanding the interplay between SGs and other biological condensates and viral replication, the role of SG formation during coronavirus infection remains poorly understood. Several proteins from different coronaviruses have been shown to suppress SG formation upon overexpression, but there are only a handful of studies analyzing SG formation in coronavirus-infected c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 108 publications
1
29
0
Order By: Relevance
“…This model was consistent with the reported mechanism governing nucleocytoplasmic shuttling of PABPC1 [5658]. It was also informed by our analysis of the SARS-CoV2 host shutoff protein Nsp1 that causes similar nuclear PABPC1 relocalization [59], and a previously proposed model for nuclear PABPC1 accumulation caused by KSHV host shutoff nuclease SOX and its homologue from the murine gammaherpesvirus 68 (MHV68) called muSOX [15]. That work by the Glaunsinger group and their later studies also described how aberrant nuclear accumulation of PABPC1 caused hyperadenylation of mRNAs [15,56].…”
Section: Discussionsupporting
confidence: 90%
“…This model was consistent with the reported mechanism governing nucleocytoplasmic shuttling of PABPC1 [5658]. It was also informed by our analysis of the SARS-CoV2 host shutoff protein Nsp1 that causes similar nuclear PABPC1 relocalization [59], and a previously proposed model for nuclear PABPC1 accumulation caused by KSHV host shutoff nuclease SOX and its homologue from the murine gammaherpesvirus 68 (MHV68) called muSOX [15]. That work by the Glaunsinger group and their later studies also described how aberrant nuclear accumulation of PABPC1 caused hyperadenylation of mRNAs [15,56].…”
Section: Discussionsupporting
confidence: 90%
“…Thus far, only three papers have described the functions of the NS proteins of HCoV-OC43 in the context of HCoV-OC43 biology [ 38 , 44 , 45 ]. Mounir et al characterized the nucleotide and amino acid sequences of NS2 [ 45 ].…”
Section: Genome Structure Of Hcov-oc43mentioning
confidence: 99%
“…Labonte et al confirmed the expression of the NS2 protein in HCoV-OC43-infected HRT-18 cells. Dolliver et al showed the inhibitory ability of the NS1 protein of HCoV-OC43 against stress granule formation [ 44 ]. Since most of early studies examined the functions of the structural proteins of HCoV-OC43, we focus on the description of characteristics of the structural proteins of HCoV-OC43 in the following section.…”
Section: Genome Structure Of Hcov-oc43mentioning
confidence: 99%
“…Some studies agree that the N protein could disrupt SG formation by sequestering G3BP1/2 from interacting with other proteins (Stukalov et al, 2021;Kim et al, 2022). The non-structural protein 1 (Nsp1) of the virus can decrease the level of G3BP1, which is associated with nuclear accumulation of the SG-nucleating protein TIAR (Dolliver et al, 2022). Besides, methyltransferases 1 (PRMT1) methylates SARS-CoV-2 N protein at residues R95 and R177.…”
Section: Viruses Inhibit Sg Formationmentioning
confidence: 99%